Effect of positive surgical margins on biochemical failure, biochemical recurrence‐free survival, and overall survival after radical prostatectomy: Median long‐term results. Issue 10 (23rd May 2014) - Huri, Emre; Aydogmus, Yasin; Doluoglu, Omer Gokhan; Dadali, Mumtaz; Karakan, Tolga; Emir, Levent; Germiyanoglu, Cankon
Abstract: The aim of this study was to investigate the median long‐term effects of positive surgical margin (PSM) and other prognostic factors on biochemical recurrence‐free survival, overall survival, and biochemical failure in patients who underwent radical prostatectomy. Our study included 121 patients with pT2‐3N0 disease treated between March 2006 and August 2012. The patients were divided into two groups: those with PSM and those with negative surgical margin (NSM). We analyzed the age, clinical and pathological stages, preoperative and postoperative Gleason scores, duration of the follow‐up, adjuvant chemo‐/radiotherapy, biochemical failure, biochemical recurrence‐free survival, and overall survival in these patients. PSM was found in 25 (20%) patients, whereas 96 patients had NSM. The median follow‐up time was 46.6 months (range 12–72 months) for the PSM group and 48.3 months (range 7–149 months) for the NSM group. The biochemical failure rate was 24% in the PSM group and 8.3% in the NSM group ( p  = 0.029). The biochemical recurrence‐free survival was found as 76% in the PSM group and 91.7% in the NSM group. The difference between the groups was not statistically significant ( p  = 0.06). The overall survival was 100% in both groups. The surgical margins of the radical prostatectomy material is an important pathological indicator for biochemical failure at mid long‐term follow‐up. We did not find any effect of PSM on overall survival or biochemical recurrence‐free survival.